Physico-Chemical Characteristics of Lampung Natural Zeolite Functionalized Mercapto-Silane - Azizah, Yulyani Nur; Rachman, Faizal (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2023)
Lampung natural zeolite (ZAL) is a potential adsorbent for metal pollutants.However, its adsorption capacity is still low due to the presence of impurities that cover the pores and active sites on its surface. To improve the adsorption performance, especially on soft acid Lewis metals/cations, ZAL needs to be activated and functionalized with organosilanes containing thiol groups (-SH) as soft Lewis bases such as (3-mercaptopropyl) trimethoxysilane (MPTMS). This study aims to determine the physicochemical properties of organosilane-modified natural zeolites. The MPTMS silanization process in ethanol: water (1:1, v/v) media was carried out on ZAL activated with 1 M HCl. Qualitatively, the success of the functionalization can be directly observed from the dispersion of the zeolite in organic and aqueous phases, where the hydrophobicity of the silane-modified zeolite (ZM-EA) increased compared to the natural zeolite. The functional group analysis results showed typical peaks of S-H and C-H at 2554 and 2930 cm-1. MPTMS functionalization produced five peaks of the typical diffraction pattern of clinoptilolite at 2θ: 10,4o; 17,8o; 22,8o; 28,3o; 30,5o; dan 32,4o. SEM-EDX results on ZM-EA showed the presence of a sulfur component of 4.75% (% At) with a Si/Al ratio >7.